2019
DOI: 10.1213/ane.0000000000003316
|View full text |Cite
|
Sign up to set email alerts
|

Development and Initial Evaluation of a Novel, Ultraportable, Virtual Reality Bronchoscopy Simulator: The Computer Airway Simulation System

Abstract: We describe the design, development, and initial evaluation of the CASS-a new, ultraportable, affordable, VR bronchoscopy simulator. The simulator's face validity was supported by excellent assessments from senior anesthesiologists with regard to anatomical realism, quality of graphics, and handling performance, even though some future refinements are required. All the practitioners agreed on the significant educational potential of the CASS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Successful performance of ATI has been shown to be independent of seniority, but related to experience . There are many strategies used for training in the technical aspects of ATI, including the use of manikins, simulators, cadavers and patients . All anaesthetists should seek every opportunity to attain and maintain skills in ATI and all departments should support this (Grade C).…”
Section: Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…Successful performance of ATI has been shown to be independent of seniority, but related to experience . There are many strategies used for training in the technical aspects of ATI, including the use of manikins, simulators, cadavers and patients . All anaesthetists should seek every opportunity to attain and maintain skills in ATI and all departments should support this (Grade C).…”
Section: Trainingmentioning
confidence: 99%
“…There are many strategies used for training in the technical aspects of ATI, including the use of manikins, simulators, cadavers and patients [59,[155][156][157][158][159][160][161]. All anaesthetists should seek every opportunity to attain and maintain skills in ATI and all departments should support this [1] (Grade C).…”
Section: Trainingmentioning
confidence: 99%
“…15,16 IVE-based anesthesia training has been reported for procedural areas such as bronchoscopy, central line insertion, and regional anesthesia simulators. [17][18][19][20] Studies investigating such procedural training have shown that practicing technical skills in virtual environments can lead to effective knowledge Cost for creation and equipment can vary from a few hundred to thousands of dollars, depending on the level of immersion and complexity.…”
Section: Technical Skillsmentioning
confidence: 99%
“…IVE-based anesthesia training has been reported for procedural areas such as bronchoscopy, central line insertion, and regional anesthesia simulators. 17–20 Studies investigating such procedural training have shown that practicing technical skills in virtual environments can lead to effective knowledge acquisition and retention with subsequent successful clinical application. 15,17 Furthermore, IVEs can be easily manipulated, allowing iterative skill-building within evolving virtual scenarios.…”
Section: Ives and Anesthesia Educationmentioning
confidence: 99%
“…Cheaper models have been developed with similar results. 23 Simulators regardless of low or high fidelity have demonstrated these positive outcomes in procedural training 24,25 Steinfort et al used low fidelity three-dimensional (3D)printed anatomic airway model where participants performed bronchoscopy and were assessed according to time required to navigate to a target bronchus and were successful in assessing bronchoscopic dexterity and reliably discriminate between different levels of skill in performing bronchoscopic navigation and airway inspection. 26 3D printed models in other studies have demonstrated similar feasibility and results.…”
Section: Incompetentmentioning
confidence: 99%